Aerobic oxidative decyanation–amidation of arylacetonitriles with urea as a nitrogen source. Issue 3 (19th December 2016) - Xu, Xuezhao; Li, Bingnan; Zhao, Yingwei; Song, Qiuling
Abstract : An iron-catalyzed aerobic oxidative amidation of aryl acetonitriles to afford amides is achieved using urea as a convenient nitrogen source. Abstract : An iron-catalyzed aerobic oxidative amidation reaction of the inert C–CN bond of aryl acetonitriles to afford aryl amides has been developed. Urea is used as an efficient and convenient nitrogen source. This reaction provides practical access toward amide synthesis.